Ghana. - Briggs, Philip, ....- (Chalfont St Peter : Bradt Travel Guides, 2010)
Ghana is an ideal destination for first-time visitors to Africa; rich in little-visited national parks, forest reserves, cultural sites and scenic waterfalls, blessed with bleached white beaches and lush rain forests of the Atlantic coastline. This stand-alone guide, the only one available, caters for both the budget backpacker and the luxurious resort wallower. Including authoritative history and wildlife sections, updated accommodation and restaurant recommendations and a wealth of background and practical information, Bradt's Ghana covers the country with unrivalled detail and knowledge. Ghana defeated Sudan 2-0 in Accra to become the first African team to reach the 2010 World Cup in South Africa. What better time to catch this friendly, English-speaking and hassle-free country as it revels on a soccer high?
Keywords: Ghana -- Reisgidsen